Contribution of secondary school geography assessment strategies in mitigating climate change in Uganda - Alex, Ronald Mwangu; Kagoda Alice Merab; Mugimu, Christopher Byalusaago (International Journal of Education and Research, 2019)
Climate change is one of the most pressing challenges of the 21st century. The changing climate affects all aspects of human livelihoods. Effects of climate change are most felt in developing countries due to low awareness and lack of access to information on climate change. Climate change is a major concern to education policy makers and curriculum developers. Education has a role to play in building individual and social capacities for adapting and mitigating climate change. The purpose of education in Uganda is to eradicate illiteracy and to equip the individual with basic skills and knowledge to exploit the environment for self-development as well as national development, for better health, nutrition and family life, and the capability for continued learning. To mitigate climate change, all elements of the education system namely; objectives, content, teaching methods and assessment strategies must lend themselves to building capacities of the learners. This study reveals that the assessment strategies used by geography teachers largely contribute to acquisition of knowledge and hardly develop skills and values/attitudes for mitigating climate change among learners.